La place des acteurs dans la recherche collaborative. Étude du dispositif de médiation par les pairs en milieu scolaire : modalités et perspectives du faire ensemble - Sylvie Condette (Recherches en Éducation)
The injunction to collaborate has become a tireless political leitmotif in contemporary organizations - whatever their legal status - as if collaboration between several people for a common object were necessarily self-evident, and as if, with the help of repeated arguments, the incantation towards teamwork could immediately produce the expected effects. However, there is no question of denying the value of collaboration, and even less of evading the benefits of working together. Nevertheless, it is necessary, when working together, to take enough time to define jointly what collaboration means and to give it prior consistency in order to agree on its meaning and the objectives that are aimed at and shared. This is what I propose to study through the implementation of peer mediation within French schools.